Figments of reality : - Stewart, Ian (Cambridge University Press, 1997)
The unique partnership of Ian Stewart and Jack Cohen return with an exhilarating and entertaining exploration of how mind, language and culture evolved. Providing a fresh outlook on these topical questions, they develop new and intriguing insights into the nature of evolution, science and humanity. From reviews of their previous bestseller, The Collapse of Chaos:'A host of new and thought-provoking ideas ... as good an introduction to [the] science of the future as any you're likely to find.' Nature